HARDNESS AND TENSILE BEHAVIOR OF FRICTION STIR WELDED ALUMINUM AA6351 ALLOY (Journal of Mechanical Engineering, 2014)
Friction Stir Welding (FSW) is a solid state welding process gaining more applications in various industries due to better quality of the joint as it has no effect on parent metal. In FSW process a non consumable rotating welding tool is used to generate frictional heat between tool and abutting surface of work piece and plastic dissipation of energy to accomplish the weld. Being a solid state joining process, friction stir welding process offers various advantages like low distortion, absence of melt related defects, high joint strength etc. as compared to other conventional fusion welding techniques.Experiments were conducted on 6 mm thickness Aluminum AA6351-T4, commercially available plates. The seplates are joined by FSW along the rolling direction (longitudinal weld orientation) and across the rolling direction (transverse weld orientation). The hardness and tensile strength results of the weldments are presented. Results show superior mechanical properties for the joints with plates along the rolling direction as compared with the joints obtained by across the rolling direction.DOI: http://dx.doi.org/10.3329/jme.v44i1.19494